ANALISIS KEMAMPUAN BERPIKIR KRITIS MATEMATIK SISWA SMP PADA MATERI SEGITIGA DENGAN PENDEKATAN METAPHORICAL THINKING - Dina Oktoviani Mardiyanti; M Afrilianto; Euis Eti Rohaeti (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2018)
This research is based on facts in schools on implementing Kurtilas, students are demanded to think more scientific. Kurtilas is concerned about critical thinking skill of mathematics for solving problems. To gain increased on critical thinking skill of Mathematics, the researcher used Metaphorical Thinking by Deskriptif Kualitatif method. This research was conducted at SMPN 22 Depok and used VII grade as the research samples. The qualitative data was gained from trying out the result of students critical thinking skill of mathematics. The research result shows that Metaphorical Thinking Approach can increase critical thinking skill of mathematics of junior high school students on the triangular material.